INSECT-PEST COMPLEX OF FLEMINGIA SEMIALATA ROXB - A BUSHY HOST FOR LAC CULTIVATION - S. C. MEENA; K. K. SHARMA; A. MOHANASUNDARAM; VERMA , SWETA; MD. MONOBRULLAH (The Bioscan, 2014)
Flemingia semialata Roxb., a small bushy shrub is a valuable host plant for lac insect, Kerria lacca (Kerr), is mainly grown for kusmi lac cultivation. Globally, it is planted for conservation of soil and as a fodder crop. Not much information is available on insect- pests of semialata plant. Therefore, a study was planned to document the insect pests of semialata plant. A pest complex of about 32 insect pests belonging to six orders and 20 families has been recorded. All the major parts of this legume plant viz. pod/seed, leaf, stem and root were found to be infested but most of the insects were foliage feeders. Out of 32 insects-pests, 23 have been recorded as foliage feeders, 7 as sap suckers and one each as pod and root feeders.